Analysis of oxidative phosphorylation complexes in cultured human fibroblasts and amniocytes by blue-native-electrophoresis using mitoplasts isolated with the help of digitonin - Klement, P; Nijtmans, L G; Van den Bogert, C; Houstĕk, J (Analytical biochemistry, 1995)
The electrophoretic method of Schägger and von Jagow (Anal. Biochem. 199, 233-231 (1991) was adapted to allow analysis of enzymes of the respiratory chain and the ATP-synthase in cultured human skin fibroblasts and amniocytes. The cells were fractionated with digitonin and mitoplasts were isolated and used for electrophoresis. The purification of mitoplasts and the resolution by electrophoresis of the oxidative phosphorylation complexes were optimal when 0.8-1.6 mg of digitonin/mg protein was used. Intact complexes I, III, IV, and V were clearly separated by blue native-polyacrylamide gel electrophoresis (PAGE) in the first dimension and their individual subunits by tricine-sodium dodecyl sulfate-PAGE in the second dimension. Approximately 10(6) fibroblasts or amniocytes (0.4-0.6 mg protein) were sufficient for complete analysis of the oxidative phosphorylation complexes using detection by staining and by Western blotting. Comparable resolution was obtained with other cell types. Studies of fibroblasts from patients with cytochrome c oxidase deficiency demonstrated the usefulness of the method for diagnosis of mitochondrial disorders.
Keywords: elektroforéza v polyakrylamidovém gelu; kultivované buňky; Electron Transport; mitochondrie; těhotenství; Digitonin; plodová voda; oxidativní fosforylace; transport elektronů; Amniotic Fluid; Oxidative Phosphorylation; Enzymes; Cells, Cultured; Electrophoresis, Polyacrylamide Gel; ženské pohlaví; digitonin; Humans; Pregnancy; Skin; Fibroblasts; enzymy; Mitochondria; Female; kůže; lidé; fibroblasty